The learning brain : memory and brain development in children - Klingberg, Torkel, 1967- (Oxford University Press, 2013)
Despite all our highly publicized efforts to improve our schools, the United States is still falling behind. We recently ranked 15th in the world in reading, math, and science. Clearly, more needs to be done. In The Learning Brain, Torkel Klingberg urges us to use the insights of neuroscience to improve the education of our children.